KINERJA DAN KOMPETENSI GURU DALAM PEMBELAJARAN - Ismail, Muh. Ilyas (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2010)
The performance and competence of a teacher has been an important point to discuss due to the fact that it can be a legal aspect in designing and developing performance and competence of teachers. Performance is the extent to which a teacher has achieved in terms of working responsibility, in other word, a teacher’s working achievement. Hence, teachers with high performance are those who master teaching material and the method of teaching. Teacher’s performance can be assessed by three indicators: the mastery of teaching material, teaching management, and working commitment. While the teacher’s competences based on the Constitution number 14/2005 are pedagogic competence, personal, social and professional competence.